Brand New - Ed Pavitt (Singapore V&A publications, 2001)
Originally published to coincide with a major V&A exhibition, "Brand New" takes a look at contemporary consumer culture and the proliferation of brand identities which affect all our daily lives at the beginning of the 21st century. Ranging across fashion, design and media, "Brand New" sets out some provocative debates about brands, design and consuming habits. Five key sections look the economics and business of branding; personal and social identities in a global, commodified world; the shopping experience from mall to website and the ethical and social questions for both brand and consumer. 20 short features complement the main text, presenting snapshots of retail, branding and consumer behaviour from around the world. Critics, historians, anthropologists, sociologists, designers as well as voices from the business world offer a range of opinions on topics as diverse as shopping in China, fakes and counterfeiting, and the branding of personality. It is aimed at students and observers of modern culture and should appeal to anyone who shops as well as those with an interest in advertising, product design and fashion.
Age Group: Adult